The Role of Forecast Dispersion and Accuracy in Explaining Cross-Sectional Return Anomalies - Benardi Benardi; Ngadi Permana; Mohammad Chaidir (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This review aims to investigate the role of forecast dispersion and accuracy in explaining cross-sectional return anomalies in financial markets. By synthesizing recent theoretical and empirical research, the study examines how differences in information precision among investors lead to heterogeneous beliefs, which in turn affect asset prices and returns. The methodology involves a comprehensive literature review to identify key findings and theoretical frameworks that link forecast dispersion to market dynamics. Results indicate that higher forecast dispersion, associated with greater uncertainty and risk, correlates with higher expected returns as compensation. Conversely, accurate forecasts enhance market efficiency by reducing information asymmetry, thereby mitigating anomalies. The study also highlights theoretical models that explain anomalies like returns to skewness and disagreement through the lens of forecast dispersion. Empirical evidence supports these models, demonstrating the significant impact of forecast dynamics on asset pricing anomalies. The review concludes by emphasizing the need for further research to refine models capturing forecast dynamics and exploring the behavioral biases influencing forecast accuracy and dispersion. Understanding these factors is crucial for improving investment strategies, market efficiency, and risk management practices.